SOSIALISASI PEMBAYARAN DIGITAL (QRIS) DAN BRANDING UMKM DI DESA KUALA TOLAM - Donal Donal; Randy Prayogi; Hisam Fauzi; Nur Huda Ananda Prijuliantoro; Nurfa Sepiyani; Stevani Kristin; Dewi Chytia Lumban Tobing; Anisha Rahmania; Nadila Rose; Bening Embun Diniari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
In an ever-evolving digital era, technological advancements have transformed the way we conduct transactions and engage in business activities. This research focuses on two interrelated aspects: the socialization of digital payments through QRIS (Quick Response Code Indonesian Standard) and the implementation of branding for Micro, Small, and Medium-sized Enterprises (MSMEs) in rural areas. Digital payments have expanded access to more efficient financial services, while branding assists MSMEs in competing in an increasingly competitive market. The primary objective of this research is to analyze the impact of the socialization of digital payments (QRIS) on the growth of rural MSMEs and how branding can enhance their competitiveness. Additionally, the research assesses the overall economic impact of digital payment socialization on rural economies. The research findings indicate that the socialization of digital payments (QRIS) has had a positive impact on the growth of rural MSMEs, particularly in terms of increased transaction volumes and income. Furthermore, MSME branding has contributed to improving their competitiveness by establishing a strong brand identity, enhancing product or service quality, and expanding market reach. This research provides valuable insights into the role of digital technology in advancing the MSME sector in rural areas and offers guidance and recommendations to government authorities, business stakeholders, and academics on harnessing digital payments and branding in this context